2015
DOI: 10.1007/s00285-015-0907-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical properties of a minimally parameterized mathematical model for metronomic chemotherapy

Abstract: A minimally parameterized mathematical model for low-dose metronomic chemotherapy is formulated that takes into account angiogenic signaling between the tumor and its vasculature and tumor inhibiting effects of tumor-immune system interactions. The dynamical equations combine a model for tumor development under angiogenic signaling formulated by Hahnfeldt et al. with a model for tumor-immune system interactions by Stepanova. The dynamical properties of the model are analyzed. Depending on the parameter values,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
(43 reference statements)
0
25
0
Order By: Relevance
“…More recently, Urszula Ledzewicz and Heinz Schättler have tackled the problem of combining two classes of anti-cancer drugs, one hitting the tumour cell population directly, and another one indirectly, choking it by an antiangionetic effect on its vascular environment, see, e.g., [163]. Furthermore, the effects of metronomic therapy may be compared with those of the more classic maximal tolerated dose (MTD) [23] still in use in most clinical oncology departments [229]. These studies, based on the Hahnfeldt model [116] or some of its variants, that include both the tumour cell population and its environment considered as the tumour carrying capacity as a target for antiangiogenic drugs, have the remarkable feature to propose exact optimal solutions when it is possible.…”
Section: Ordinary Differential Equations and Delay-differential Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Urszula Ledzewicz and Heinz Schättler have tackled the problem of combining two classes of anti-cancer drugs, one hitting the tumour cell population directly, and another one indirectly, choking it by an antiangionetic effect on its vascular environment, see, e.g., [163]. Furthermore, the effects of metronomic therapy may be compared with those of the more classic maximal tolerated dose (MTD) [23] still in use in most clinical oncology departments [229]. These studies, based on the Hahnfeldt model [116] or some of its variants, that include both the tumour cell population and its environment considered as the tumour carrying capacity as a target for antiangiogenic drugs, have the remarkable feature to propose exact optimal solutions when it is possible.…”
Section: Ordinary Differential Equations and Delay-differential Modelsmentioning
confidence: 99%
“…The relevance of the use of metronomic therapy as an alternative to maximum tolerated dose of cytotoxic drugs in chronic forms of cancer is a question that has been actively studied for some time [23,199], and more recently with optimal control methods [229]. Its achievements were firstly attributed to angiogenic effects of cytotoxic drugs [154], then to effects of low doses of chemotherapy on stimulating the immune response [199], in particular due to the effects of tumour lysates on the participation of memory T-cells in the immune response [265].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…To date, only a few mathematical models of metronomic therapy have been published, none of which accounts for interactions among cancer cells, CSCs, immune cells, and tumor blood vessels (26)(27)(28)(29)(30)(31)(32). To this end, we have developed a mathematical model for tumor growth that accounts for three different phenotypes of cancer cells-nonstem cancer cells (CCs), CSCs (which are more resistant to drugs, hypoxia, and the immune system), and CCs that are induced by chemotherapy to acquire a more stem-like phenotype, which we refer to as treatment-induced cancer cells (ICCs) (33), as well as immune cells [natural killer (NK) cells, CD8 + T cells, and Tregs], tumor vasculature, and their interactions (Fig.…”
mentioning
confidence: 99%
“…In the paper [51] we have analyzed the system (29)- (31) for a constant metronomic dosing, u.t/ D u Á const, from a dynamical systems point of view and have shown that this system exhibits a similar wide range of dynamical behaviors as the model considered in Sect. 3 and encompasses the same variety of medical scenarios.…”
Section: A Combined Mathematical Model and Metronomic Chemotherapymentioning
confidence: 95%
“…This is the case we consider here. [51]. We again call the low equilibrium point benign and its region of attraction the benign region and call the high equilibrium point malignant and its region of attraction the malignant region.…”
Section: A Combined Mathematical Model and Metronomic Chemotherapymentioning
confidence: 98%